Observation of cabibbo-suppressed two-body hadronic decays and precision mass measurement of the Ω0c baryon - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2024)
The first observation of the singly Cabibbo-suppressed Ω0𝑐→Ω−⁢𝐾+ and Ω0𝑐→Ξ−⁢𝜋+ decays is reported, using proton-proton collision data at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.4 fb−1, collected with the LHCb detector between 2016 and 2018. The branching fraction ratios are measured to be ℬ⁡(Ω0𝑐→Ω−⁢𝐾+)ℬ⁡(Ω0𝑐→Ω−⁢𝜋+)=[6.08±0.51⁢(stat)±0.40⁢(syst)]%,ℬ⁡(Ω0𝑐→Ξ−⁢𝜋+)ℬ⁡(Ω0𝑐→Ω−⁢𝜋+)=[15.81±0.87⁢(stat)±0.44⁢(syst)±0.16⁢(ext)]%. In addition, using the Ω0𝑐→Ω−⁢𝜋+ decay channel, the Ω0𝑐 baryon mass is measured to be 𝑀⁡(Ω0𝑐)=2695.28±0.07⁢(stat)±0.27⁢(syst)±0.30⁢(ext) MeV, improving the precision of the previous world average by a factor of 4.
Im Text ist "0" hochgestellt, "c" tiefgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, L. Carus, R. Caspary, C. Cocha Toapaxi, M. De Cian, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, G. Tuci, D.J. Unverzagt, U. Ulrich, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 11.10.2024